2022
DOI: 10.1186/s40834-022-00193-w
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk behaviour among school-going adolescents in Sierra Leone and Liberia: a secondary analysis of the 2017 Global school-based student health surveys

Abstract: Background Sierra Leone and Liberia have experienced civil wars and, recently, Ebola outbreaks that led to profound economic hardship, psychopathologies and family disruptions. These factors are associated with sexual risk behaviours among youths. However, there is very little information on sexual risk behaviour among Sierra Leonean and Liberian school-going adolescents. The present study assessed the prevalence and determinants of sexual risk behaviours among school-going adolescents (10–19 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Males may experience social pressure to conform, make a favourable impression on others or cope with stress by consuming alcohol. On the other hand, females may encounter increased social shame, discrimination or violence if they consume alcohol, particularly in conservative or religious groups 46. Males may have a higher likelihood of associating with those individuals who consume alcohol or being exposed to alcohol in their social environments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Males may experience social pressure to conform, make a favourable impression on others or cope with stress by consuming alcohol. On the other hand, females may encounter increased social shame, discrimination or violence if they consume alcohol, particularly in conservative or religious groups 46. Males may have a higher likelihood of associating with those individuals who consume alcohol or being exposed to alcohol in their social environments.…”
Section: Discussionmentioning
confidence: 99%
“…Males may have a higher likelihood of associating with those individuals who consume alcohol or being exposed to alcohol in their social environments. They may also have easier access to alcohol, whether obtained legally or illegally, compared with females 46. Additionally, males may be more susceptible to psychological distress and trauma as a result of poverty, violence, warfare and displacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found an association between cannabis use and sexual risk behaviours among school-going adolescents in Sierra Leone. School-going adolescents who engage in sexual risk behaviours might use cannabis to cope with emotional distress or adverse consequences arising from those behaviours [ 29 ]. Policymakers in Sierra Leone should provide comprehensive and age-appropriate sexual health education to promote safe sexual practices.…”
Section: Discussionmentioning
confidence: 99%